7. NUTRITIONAL CHARACTERISTICS AND SUPPLEMENTATION IN CHILDREN WITH BILIARY ATRESIA TREATED AT CHILDREN’S HOSPITAL 2 (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to describe the nutritional characteristics and supplementation strategies in children diagnosed with biliary atresia who are being treated at Children’s Hospital 2.Methods: A cross-sectional study was conducted involving 120 children with biliary atresia under follow-up care at the Hepatobiliary Pancreatic Department of Children’s Hospital 2 from March to April 2024. Nutritional assessments were carried out through direct interviews with caregivers using a structured questionnaire and dietary logs. The nutritional composition of the diets was analyzed using Eiyokun software.Results: The majority of patients consumed formula milk, with 40.6% using age-appropriate formulas and only 6.6% using liver-specific formulas. Supplementation with MCT oil, maltodextrin, and legumes in porridge or formula was reported at rates of 29.2%, 13.3%, and 40%, respectively. Notably, no children received BCAA (branched-chain amino acids) supplementation. Among the sample, 47.5% underwent a nutritional assessment, and 56.1% were assessed less than once every six months. Only 21.7% of children had individualized nutrition plans, and of those, 57.7% adhered to their plans over 80% of the time.Conclusion: The use of liver-specific formulas was very low, and nutritional support with MCT oil, maltodextrin, BCAA, or legume protein was limited. Dietary assessments were infrequent, with most occurring less often than once every six months. Individualized dietary plans were rare, and adherence to these plans was limited. Overall, early and regular nutritional support for children with biliary atresia at Children’s Hospital 2 is currently inadequate and requires significant improvement.